Elucidating the molecular mechanisms underlying the endothelial-to-hematopoietic transition - Greder, L (2017)
Definitive hematopoietic stem and progenitor cells (HSPCs) are generated de novo from a subset of endothelium, the hemogenic endothelium (HE), via a process called the endothelial-to-hematopoietic transition (EHT). To facilitate the study of HE throughout this process, our lab generated a Runx1 enhancer-reporter mouse model (23GFP) to dissect the cellular and molecular events that underlie EHT. Previous work in the lab highlighted that HE undergoes dynamic fate changes already early in development characterized by two distinct states, a competent state (cHE) and a specifying stage (sHE). In the context of EHT, this study rewrote the timeline of hematopoietic commitment during EHT and showed this is initiated in sHE before the proHSC and type I and type II preHSC stages. My aim was to identify and characterize the gene regulatory interactions (GRIs) underlying these cell fate transitions. We reasoned that integration of expression (RNA-seq) and chromatin profiles (ATAC-seq) would facilitate identification of these GRIs. After validating and characterizing the data sets, we focused on TFs where the timing and appearance of the motif coincided with expression of the TF and identified these as putative regulators of accessibility and subsequent changes in gene expression. Focusing on two key cell fate transitions: (1) cHE to sHE and (2) sHE to proHSC, we generated GRI maps. Analysis of these regulatory interactions identified putative causative regulators, including Bcl11a, Mef2c, Ikzf1, and Ikzf2. Looking more closely at Ikzf1, we identified a -28 element required for proper Ikzf1 expression. Interestingly, -28 activity was Runx1-dependent. Further investigation identified Notch signaling as a downstream target of the novel the Runx1-Ikzf1 regulatory axis. Finally, interrogation of this regulatory axis using genetic perturbation revealed a complex interaction whereby Runx1 and Ikzf1 work both individually and synergistically to regulate Notch during in vitro EHT.